Enhancing Students' Conceptual Understanding of Newton Law with Conceptual Problem Solving Learning: An Experimental Study - Diyana, Tsania Nur; Sutopo, Sutopo (International Journal of Education and Teaching Zone, 2024)
This study aims to examine the effectiveness of Conceptual Problem Solving-based learning in improving student conceptual understanding of Newtonian mechanics. The quasi-experimental method with a nonrandomized control group pretest-posttest design was used to compare students conceptual in the experimental and control class. The subjects in this study were 69 first-year students of the Physics Education study program at one of the state universities in Yogyakarta. Force Concept inventories are used to assess students conceptual understanding of Newtonian mechanics. The findings revealed that there was significant difference in the increase in students conceptual understanding between the experimental and control groups. The increase in conceptual mismatch in experimental class students using CPS learning was higher (N-gain = 0.33) compared to control class students using direct instruction learning (N-gain = 0.11), although both groups experienced an increase. This study provides a real picture that the CPS technique can be used as a more successful strategy to improve the quality of physics learning, especially in improving knowledge of basic topics that are often difficult for students to understand, one of which is Newton's Law.